2008
DOI: 10.1007/s11695-008-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Results and Complications After Swedish Adjustable Gastric Banding in Older Patients

Abstract: At 7-year follow-up, for older patients, SAGB is an effective bariatric procedure for achieving weight loss. Nevertheless, based on the high complication and reoperation rate, a gastric band-specific patient selection will be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…ICU stay was short when required, and overall hospital stay averaged less than 2 days. A small number of studies exist detailing complication rates after LGB specific to elderly patients (see Table 5) ( [15,18,[24][25][26]29]). Major complication rates are usually reported at <5% with minors from 5 to 25%.…”
Section: Safety and Complicationsmentioning
confidence: 99%
“…ICU stay was short when required, and overall hospital stay averaged less than 2 days. A small number of studies exist detailing complication rates after LGB specific to elderly patients (see Table 5) ( [15,18,[24][25][26]29]). Major complication rates are usually reported at <5% with minors from 5 to 25%.…”
Section: Safety and Complicationsmentioning
confidence: 99%
“…[59][60][61][62][63][64][65][66][67][68][69][70] Band slippage or band prolapse occurs when part of the stomach herniates through the band at the top of the stomach. This occurs in about 4% (1.0%-6.5%) of patients in recent studies, with older studies showing a much higher rate of this complication.…”
Section: Late Complicationsmentioning
confidence: 99%
“…This occurs in about 4% (1.0%-6.5%) of patients in recent studies, with older studies showing a much higher rate of this complication. 64,65,[71][72][73] The reason for this dramatic reduction in slippage rate is attributed to the use of the pars flaccida technique instead of the less frequently used perigastric approach for the insertion of the gastric band around the proximal stomach. Several studies have demonstrated a reduction in the number of slips from as high as 15% down to 2% simply by this change of technique.…”
Section: Late Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal dilation, as assessed by barium swallow, appears as a frequent complication of gastric banding, ranging from almost 6% in patients younger than 25 years old to more than 15% in patients older than 50 years [1,4,5]. It is, however, not clear from the literature how often esophageal dilation is responsible for symptoms such as dysphagia, vomiting or gastroesophageal reflux disease (GERD)-like symptoms (regurgitations).…”
mentioning
confidence: 99%